1996
DOI: 10.1083/jcb.133.4.879
|View full text |Cite
|
Sign up to set email alerts
|

Associations among PH and SH3 domain-containing proteins and Rho-type GTPases in Yeast.

Abstract: Abstract. The src homology region 3 (SH3) domainbearing protein Bemlp and the Rho-type GTPase Cdc42p are important for bud emergence in Saccharomyces cerevisiae. Here, we present evidence that through its second SH3 domain, Bemlp binds to the structurally and functionally similar proteins Boilp and Boi2p, each of which contain an SH3 and a pleckstrin homology (PH) domain. Deletion of BOll and BOI2 together leads to impaired morphogenesis and poor viability. A PH domain-bearing segment of Boilp that lacks the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(157 citation statements)
references
References 66 publications
(109 reference statements)
4
153
0
Order By: Relevance
“…binding protein). Data base analysis detected two yeast genes whose protein products possessed significant homology to MTBP: BOI1 and BOI2 (36,37). The two proteins encoded by these genes (Boi1p and Boi2p, respectively) exhibit an overall amino acid identity of 38%, but this is concentrated into four regions (I-IV) that possess identities of 71, 65, 78, and 69%, respectively.…”
Section: Fig 2 Mtbp Is Expressed In a Variety Of Tissues And Fulllmentioning
confidence: 99%
See 1 more Smart Citation
“…binding protein). Data base analysis detected two yeast genes whose protein products possessed significant homology to MTBP: BOI1 and BOI2 (36,37). The two proteins encoded by these genes (Boi1p and Boi2p, respectively) exhibit an overall amino acid identity of 38%, but this is concentrated into four regions (I-IV) that possess identities of 71, 65, 78, and 69%, respectively.…”
Section: Fig 2 Mtbp Is Expressed In a Variety Of Tissues And Fulllmentioning
confidence: 99%
“…MTBP Inhibits Cell Growth-Several MDM2-binding proteins are regulators of cell growth; and indeed, both of the MTBP partial homologs (Boi1p and Boi2p) have been shown to have growth inhibitory activity (36,37). Therefore, we investigated the effect of MTBP expression on cell growth in culture.…”
Section: Fig 2 Mtbp Is Expressed In a Variety Of Tissues And Fulllmentioning
confidence: 99%
“…Through multiple protein interaction domains, these proteins may facilitate transient protein complex formation but are unlikely to act as static reference site for the localization of the bound proteins. One example is Bem1, which has binding sites for a number of proteins involved in cell polarization, including Cdc42 GTP , Cdc24, Cla4 and Boi1,2 proteins [67,118]. Whereas Bem1 may engage in hetero-oligomeric interactions, it has been shown to rapidly cycle on and off the plasma membrane and is therefore unlikely to provide any significant anchorage for its binding partners [69].…”
Section: Scaffolds As Potential Flexible Linkagesmentioning
confidence: 99%
“…Vertebrate actin-associated proteins containing SH3 domains include proteins with structural roles such as fodrin and nebulin (Merilainen et al, 1993;Wang et al, 1996), unconventional myosins (Bement et al, 1994;Stoffler et al, 1995;Goodson et al, 1996), kinases and associated molecules (Flynn et al, 1993;Turner and Miller, 1994;Hildebrand et al, 1996), and other actin-binding proteins such as cortactin (Wu and Parsons, 1993). In S. cerevisiae, SH3-containing proteins include the actin-associated proteins Abplp (Drubin et al, 1990), Slalp (Holtzman et al, 1993), and Rvs167p (Bauer et al, 1993), as well as Bemlp and the recently identified Boilp and Boi2p, which have roles in the maintenance of normal cellular and cytoskeletal morphology (Chenevert et al, 1992;Bender et al, 1996;Matsui et al, 1996). A number of yeast proteins implicated in cytoskeletal function, including Abplp, Slalp, Boilp, Boi2p, and Srv2p (Field et al, 1990), contain proline-rich regions which include amino acid sequences similar to known binding sites for SH3 domains.…”
Section: Introductionmentioning
confidence: 99%